A COMPARISON STUDY BETWEEN DIFFERENT METHODS OF TRAVELLING WAVE INDUCTION HEATER ANALYSIS - Nasir, Bilal; Dr. A.K.M Al-Shakhli (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
The travelling wave induction heater (T.W.I.H) is a new and promising tool the field of heating rectangular workpieces. This heater has many advantages when compared with the existing techniques of heating such workpieces. But there is no available method or procedure to analyses this type of heaters In this paper different theories are adopted to study the and a novel equivalent circuit is introduced to predict the performance of this device A completely mathematıcal procedure is used in the construction of this equivalent circuit and no empirical factors were implemented.